Penggunaan Media Permainan Puzzle dalam Bimbingan Kelas Besar untuk Meningkatkan Interaksi Sosial dan Kepercayaan Diri Siswa SMA - Zainalf, Zainalf; Haryadi, Rudi; Mahfuz, Mahfuz (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2025)
Individuals who have self-confidence are generally able to motivate themselves to continue to develop into a better person from day to day. In essence, humans do not only act as individual beings, but also as social beings who need help and support from others. In living everyday life, social interaction is inseparable as a means of mutual assistance and communication. One effort that can support the development of students' social and personal skills is through cross-class guidance. This service functions as a form of prevention as well as development, with the aim of providing insight, understanding, and experience to students in social, personal, learning, and career aspects, implemented on a large scale for the same class level. This study aims to assess the effectiveness of puzzle games in the use of media through large class guidance services in improving social interaction and self-confidence of students at SMAN 1 Alalak. The research method used is a one group pre-test and post-test design, where measurements are taken before and after the treatment is given. The study population includes 230 students of SMAN 1 Alalak, with a research sample of 62 students. Data analysis was carried out using the T-Test to accurately compare the results of the pre-test and post-test. Research findings show that the use of puzzle game media in large class guidance services has proven effective in improving social interaction skills while fostering students' self-confidence